Determination of creatinine and creatine by capillary electrophoresis : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Chemistry at Massey University - Guo, Hong (Massey University, 1998)
The assessment of creatinine and creatine in biological fluids is important in the evaluation of renal and muscular functions. For routine creatinine determinations in the clinical laboratory, the most frequently used method is the spectrophotometric one based on the Jaffé reaction. However, this reaction is not specific for creatinine. For this reason, several methods have been proposed, but the elimination of interferences in the determination of creatinine has still not been achieved in some of these methods; others solved this problem either with expensive equipment that does not suit routine analysis or necessitates time-waste procedures. In this thesis capillary electrophoresis was the new tool investigated. It was applied in an attempt to achieve both the separation of creatinine from the non-creatinine 'Jaffé- reacting' chromogens and the determination of creatine in serum. Capillary zone electrophoresis was performed with detection at wavelength 480 nm to separate creatinine from the non-creatinine 'Jaffé-reacting' chromogens in urine. The principle was based upon the different migration times due to the different molecule weights, molecular sizes and charges under the applied high voltage. The picric acid was employed as part of the running buffer to allow reaction of creatinine and picrate to take place after the sample injection. This procedure eliminated the negative influence of the reaction time that is controlled manually in the common Jaffé reaction method. Therefore, compared to the Jaffé reaction method, the new method achieved more accuracy and precision in the determination of creatinine. Determination of creatinine in serum and urine were studied at a new wavelength 417 nm, which gave a higher sensitivity of detection than at 480 nm. This wavelength shift made the determination of creatinine in serum possible by capillary zone electrophoresis without the non-creatinine 'Jaffé-reacting' chromogens interfering. In this method, serum only needed a simple filtration before the analysis. Creatine was discovered to have absorption at 417 nm in alkaline medium. Moreover, specific sample stacking was introduced in this method. The sample was dissolved in a mixture of two-volumes acetonitrile and one-volume 3 % ammonium chloride to give a 10-fold enhancement of detection sensitivity.
Keywords: Creatine; Creatinine; Capillary electrophoresis